Phaonia Robineau-Desvoidy (Diptera, Muscidae, Phaoniinae): II: revisão das espécies - Coelho,Sônia Maria Prevedello (2000)
Thirty eight species are recognized in the Neotropical Region. Twenty four are redescribed and illustrated and fourteen were not redescribed, because they are well definite in the original description. A new combination for Mydaea triseta Curran, 1931 to Phaonia and the revalidation of P. nigripuncta Stein, 1911 are made. Five new synonyms are proposed: P. coquilletii (Vimmer, 1939) = P. punctinervis Stein, 1911; P. nigrocincta Stein, 1918 = P. abdita (Giglio-Tos, 1893); P. praedatoria (Snyder, 1957) = P. latinervis (Stein, 1904); P. vulgata (Albuquerque & Medeiros, 1980) = P. similata (Albuquerque, 1957); P. nigra (Albuquerque & Medeiros, 1980) = P. trispila (Bigot, 1885). A key to the neotropical species is presented for the thirty eight recognized species.